2016
DOI: 10.3748/wjg.v22.i46.10180
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and antioxidant effects of lycopene on non-alcoholic fatty liver disease in rat

Abstract: AIMTo evaluate the hepatoprotective effect of lycopene (Ly) on non-alcoholic fatty liver disease (NAFLD) in rat.METHODSA rat model of NAFLD was first established by feeding a high-fat diet for 14 wk. Sixty-five rats were randomly divided into normal group, model group and Ly treatment groups. Alanine aminotransferase (ALT), aspartate aminotransferase (AST), triglycerides (TG), total cholesterol (TC) in serum and low density lipoprotein-cholesterol (LDL-C), high density lipoprotein-cholesterol (HDL-C), free fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 39 publications
7
68
0
Order By: Relevance
“…In developed countries, NAFLD is increasing due to the incidence of obesity, and it is currently more prevalent than alcohol-induced liver disease. Several studies have reported the beneficial effect of dietary carotenoids, particularly lycopene, for the prevention and treatment of steatosis [ 3 , 6 , 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In developed countries, NAFLD is increasing due to the incidence of obesity, and it is currently more prevalent than alcohol-induced liver disease. Several studies have reported the beneficial effect of dietary carotenoids, particularly lycopene, for the prevention and treatment of steatosis [ 3 , 6 , 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it has been recommended for the treatment of NAFLD in the practical clinical guide of the European associations for the study of the liver, diabetes, and obesity (EASL-EASD-EASO) [ 5 ]. The Mediterranean diet combines marine products and grains rich in mono and polyunsaturated fats with fruits and vegetables rich in dietary bioactive antioxidants, such as polyphenols and carotenoids, which have a beneficial effect in the prevention of NAFLD, as has been shown in different animal models [ 1 , 6 , 7 , 8 ]. Interestingly, for non-provitamin A carotenoids, and particularly for lycopene (from tomato) [ 3 , 9 ], there is much experimental evidence on the prevention of steatosis and inflammation in murine models, through different mechanisms, including the scavenging activity of reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overconsumption of dietary lipids leads to abnormal lipid metabolism and increased hepatic fat accumulation, which activates the expression of cytochrome P450 2E1 (CYP2E1) and increases oxidative stress and inflammatory responses in vivo (Jiang et al, 2016;Johann et al, 2006). In addition to the increase in hepatic cytokine levels, adipose tissue can also release adipokines which have certain physiological effects.…”
Section: Introductionmentioning
confidence: 99%
“…It can reduce high-fat diet-induced steatohepatitis by reducing oxidative stress to the cells. It has been also shown that incorporation of lycopene in balanced diet prevents NAFLD [67,68]. Lycopene may be a useful functional compound for treating NAFLD by regulating hepatic lipid metabolism [69].…”
Section: Lycopene and Chronic Liver Diseasesmentioning
confidence: 99%